Correlation analysis between foveal avascular zone and near peripheral retinal hypoperfusion in multiple sclerosis: a wide field optical coherence tomography angiography study - Montorio, Daniela; Cennamo, Gilda; Carotenuto, Antonio; Petracca, Maria; Brescia Morra, Vincenzo; Costagliola, Ciro (Frontiers in Medicine, 2022)
The identification of noninvasive biomakers to investigate and monitor retinal structural and vascular changes in multiple sclerosis (MS) represents an interesting source of debate. Until now optical coherence tomography angiography (OCTA) evaluated foveal avascular zone (FAZ) and areas of retinal non perfusion only in macular region in MS patients. It could be interesting to identify possible biomarkers, useful in assessing the ischemic areas also in near peripheral retina, since FAZ enlargement and the areas of peripheral retinal non-perfusions share common pathogenic processes. In this cross-sectional study, we investigated the correlation between FAZ area and retinal vessel density (VD) in near peripheral retina by new wide field optical coherence tomography angiography (OCTA) in patients affected by relapsing-remitting multiple sclerosis (RR-MS). Moreover, we compared the FAZ area and the VD of superficial and deep capillary plexuses in fovea region and in near peripheral retina (6.4 x 6.4 mm) between RR-MS patients and healthy controls by means Solix full-range OCTA. Lastly, we also detected the changes in structural OCT parameters (ganglion cell complex and retinal nerve fiber layer). Thirty-three eyes of 33 RR-MS patients and 35 eyes of 35 healthy controls were enrolled. RRMS patients showed a lower VD in superficial capillary plexus and a significant increase in FAZ area compared with controls. The deep capillary plexus revealed a reduced VD although not statistically significant in patients respect to controls. In patients group, the FAZ area showed significantly negative correlations with VD of superficial capillary plexuses in foveal and whole region, while the FAZ area did not negatively correlate with VD of deep capillary plexus. The significant correlations among OCTA parameters could demonstrate the FAZ area as a possible biomarker for assessing the perfusion status in near peripheral retina, useful in RR-MS management. These findings could confirm the role of vascular dysfunction in pathogenetic mechanisms of MS.